Application of Fractional order PID Control in Photovoltaic Integrated Distribution Network. Issue 1 (March 2020) - Tang, Rongjiang; Xiong, Hejin; Zhang, Zixi
Abstract: When photovoltaic power generation is connected to the grid, the inverter merges the energy of the photovoltaic panel into the grid in the form of power, and the controller is required to control the DC side voltage after comparing with the maximum power tracking voltage of the photovoltaic system and tracking the DC side voltage. Based on the application of traditional PID control in the photovoltaic power generation system, we use fractional order PID to compare with it. Finally, simulation analysis verifies that fractional order PID has better dynamic and static characteristics, adaptability and robustness.